Theoretical bounce resonance diffusion coefficient for waves generated near the equatorial plane - X. Tao; X. Li (Geophysical Research Letters)
Abstract Theoretical bounce resonance diffusion coefficient for waves generated near the equatorial plane with arbitrary wave normal angle distributions is derived. Previous studies either assumed waves to cover the whole bounce trajectory or to have only one wave normal angle for a given frequency. In this work, we theoretically derive a new bounce resonance diffusion coefficient without these limitations. We demonstrate that the pitch angle diffusion from bounce resonance is significant for near‐equatorially mirroring particles using a published magnetosonic wave model. Our results suggest that the bounce resonance diffusion by magnetosonic waves could be an important mechanism for pitch angle scattering of near‐equatorially mirroring particles; therefore, it might be important to include bounce resonance with magnetosonic waves in global radiation belt modeling.